In Situ Supramolecular Self‐Assembly of Pt(IV) Prodrug to Conquer Cisplatin Resistance. (23rd April 2021) - Wang, Qian; Xiao, Meng; Wang, Dianyu; Hou, Xiaoxue; Gao, Jie; Liu, Jinjian; Liu, Jianfeng
Abstract: Drug resistance has always been a huge challenge that should be urgently conquered to improve the efficacy of anticancer drugs. Herein, a synergistic Pt(IV) prodrug, Npx‐pp ‐Pt(IV), is proposed, combining dual responsive behavior with dual drug resistance‐related pathways deactivation. First, Npx‐pp ‐Pt(IV) can in situ form a supramolecular self‐assembly with a nanofiber structure on the cancer cell surface triggered by phosphatase, which confines the drug in the tumor and effectively enhances the cellular uptake of cisplatin, resulting in a high cancer cell selectivity and an extremely low non‐targeted cytotoxicity. After being endocytosed, the self‐assembly shows glutathione‐responsive cisplatin release and reverses the IC50 of cisplatin‐resistant cancer cells to that of sensitive ones. Second, the obtained Pt(IV) prodrug can significantly damage cisplatin‐resistance cancer cells through cyclooxygenase‐2 and nuclear factor‐kappa B‐mediated apoptosis pathways, which benefit from the integration of naproxen into the prodrug. The in vivo experiment demonstrates a tumor inhibition rate of 80%. Therefore, Npx‐pp ‐Pt(IV) is a multispecific cisplatin derivative, and in situ self‐assembly is believed to be a new strategy to conquer drug resistance for clinical care. Abstract : A synergistic Pt(IV) prodrug that almost completely reverses cisplatin resistance is presented. This Pt(IV) prodrug can in situ self‐assemble on cancer cells triggered by overexpressed phosphatase to enhance cellular uptake. After endocytosis, the self‐assembly shows glutathione‐responsive cisplatin release, as well as inhibition against cisplatin resistance‐related pathways, including COX‐2 and NF‐κB.